2001
DOI: 10.1063/1.1391422
|View full text |Cite
|
Sign up to set email alerts
|

Improved energy resolution of x-ray single photon imaging spectrometers using superconducting tunnel junctions

Abstract: We present preliminary test results of optical/UV single-photon imaging spectrometers using superconducting tunnel junctions. Our devices utilize a lateral trapping geometry. Photons are absorbed in a Ta thin "lm, creating excess quasiparticles. Quasiparticles di!use and are trapped by Al/AlO V /Al tunnel junctions located on the sides of the absorber. The Ta/Al interface does not overlap the junction area. Imaging devices have tunnel junctions on two opposite sides of the absorber. Position information is obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 17 publications
1
18
0
Order By: Relevance
“…For the critical current of the SQUID we consider I c = 180 µA. Notice that recent experiments in circuit QED have considered critical currents in the range of 1−2 µA [53], however, one can increase the critical current by to a larger value or even a few orders of magnitude into the mA regime by making the junctions bigger, this would involve a trilayer fabrication process [54,55]. Moreover, we consider a flat (Ω(t) = 1) magnetic flux pulse applied to the SQUID with parametersφ = π/4 and ∆φ = 0.1φ.…”
mentioning
confidence: 99%
“…For the critical current of the SQUID we consider I c = 180 µA. Notice that recent experiments in circuit QED have considered critical currents in the range of 1−2 µA [53], however, one can increase the critical current by to a larger value or even a few orders of magnitude into the mA regime by making the junctions bigger, this would involve a trilayer fabrication process [54,55]. Moreover, we consider a flat (Ω(t) = 1) magnetic flux pulse applied to the SQUID with parametersφ = π/4 and ∆φ = 0.1φ.…”
mentioning
confidence: 99%
“…We call this diffusion-engineering. The effect was clearly seen in STJ x-ray detectors with narrow Al leads that we studied previously [8]. By simply setting the width to length ratio of the Al outdiffusion lead, one can easily set the time the quasiparticles dwell next to the junction; then , with the outdiffusion time , and is proportional to the length to width lead ratio.…”
Section: Introductionmentioning
confidence: 85%
“…It is apparent that the coordinate-dependent energy loss via escape of athermal phonons can adequately explain most of the measured spectrum. In another similar experiment using a Ta-based x-ray absorber on a solid substrate, utilizing a distributed STJ detector readout, Li et al 44 reported a spectral resolution of 12 eV (FWHM) for 6 keV x-rays, close to the theoretically achievable limit for this particular device. According to our models, the expected broadening that occurs due to the zdependent athermal phonon energy loss for this 600-nm-thick Ta absorber is ∼6 eV (FWHM).…”
Section: Discussionmentioning
confidence: 99%